Analisis Perbandingan Kinerja Protokol Routing Proactive Dan Reactive Pada Vehicular Ad Hoc Network (VANET) Di Kota Pekanbaru - Ahmad Romadan; Linna Oktaviana Sari; Ery Safrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Communication between vehicles plays an important role in increasing comfort such as reducing vehicle density and security, namely regulating vehicle speed for drivers and passengers. Advances in technology offer concepts to improve comfort and safety in driving, namely Vehicular Ad Hoc Network (VANET). However, VANET has network characteristics where the network nodes are moving very fast. In this research, a comparison of the performance of two topology-based routing protocols is performed. The topology in this research are : Optimized Link State Routing (OLSR) and Dynamic source routing (DSR) on VANET. (OLSR) is a proactive routing protocol that determines the routing table by updating every time a link changes, (DSR) belongs to a reactive routing protocol that only selects paths or updates paths only when there are new route or when a route is cut off. Both routing protocols are simulated using Network Simulator 2 (NS-2) with a scenario of changing the number of nodes. The two protocols are compared based on the parameters of the Packet delivery ratio and end-to-end delay. From the results of the study it was found that the DSR routing protocol has a better PDR value of 99.80% compared to OLSR of 99.53%, the average end-to-end delay from DSR is 0.13 seconds, while OLSR is 0.12 seconds. This shows that the DSR routing protocol is superior to the packet delivery ratio and OLSR routing protocol excels at end-to-end delay Keyword: VANET, Proactive, Reactive, OLSR, DSR